Bioconversion potential of Trichoderma viride HN1 cellulase for a lignocellulosic biomass Saccharum spontaneum. - Iqtedar, Mehwish; Nadeem, Mohammad; Naeem, Hira; Abdullah, Roheena; Naz, Shagufta; Syed, Qurat ul Ain; Kaleem, Afshan (Natural Product Research, 2015)
The industrialisation of lignocellulose conversion is impeded by expensive cellulase enzymes required for saccharification in bioethanol production. Current research undertakes cellulase production from pretreatedSaccharum spontaneumthroughTrichoderma virideHN1 under submerged fermentation conditions. Pretreatment of substrate with 2% NaOH resulted in 88% delignification. Maximum cellulase production (2603 ± 16.39 U/mL/min carboxymethyl cellulase and 1393 ± 25.55 U/mL/min FPase) was achieved at 6% substrate at pH 5.0, with 5% inoculum, incubated at 35°C for 120 h of fermentation period. Addition of surfactant, Tween 80 and metal ion Mn+2, significantly enhanced cellulase yield. This study accounts proficient cellulase yield through process optimisation by exploiting cheaper substrate to escalate their commercial endeavour.